Effectiveness of Extended or Continuous vs. Bolus Infusion of Broad-Spectrum Beta-Lactam Antibiotics for Febrile Neutropenia: A Systematic Review and Meta-Analysis - Kazuhiro Ishikawa; Koko Shibutani; Fujimi Kawai; Erika Ota; Osamu Takahashi; Nobuyoshi Mori (MDPI AG, 2023)
This systematic review aimed to compare extended infusion or continuous infusion with bolus infusion for febrile neutropenia (FN). We included clinical trials comparing extended or continuous infusion with bolus infusion of beta-lactam antibiotics as empirical treatment for FN and evaluated the clinical failure, all-cause mortality, and adverse event rates. Five articles (three randomized controlled trials (RCTs) and two retrospective studies) from 2014 to 2022 were included. Clinical failure was assessed with a risk ratio (RR) (95% coincident interval (CI)) of 0.74 (0.53, 1.05) and odds ratio (OR) (95% CI) of 0.14 (0.02, 1.17) in the 2 RCTs and retrospective studies, respectively. All-cause mortality was assessed with an RR (95% CI) of 1.25 (0.44, 3.54) and OR (95% CI) of 1.00 (0.44, 2.23) in the RCTs and retrospective studies, respectively. Only 1 RCT evaluated adverse events (with an RR (95% CI) of 0.46 (0.13, 1.65)). The quality of evidence was "low" for clinical failure and all-cause mortality in the RCTs. In the retrospective studies, the clinical failure and all-cause mortality evidence qualities were considered "very low" due to the study design. Extended or continuous infusion of beta-lactam antibiotics did not reduce mortality better than bolus infusion but was associated with shorter fever durations and fewer adverse events.